ダイ9ジ ナンキョク チイキ カンソクタイ ナツタイ ホウコク 1967-1968 - 清野, 善兵衛; セイノ, ゼンベイ; SEINO, Zenbei (国立極地研究所, 1968)
P(論文) The 9th Japanese Antarctic Research Expedition (1967-1968), consisting of fourty members, was led by Mr. Masayoshi MURAYAMA, also leading the wintering party of twenty eight men. The deputy leader (the author) led the summer party of twelve members. On November 25, 1967, the icebreaker FUJI under command of Rear Admiral Toshiharu HONDA, with fourty expedition members and four news reporters, left Tokyo and headed for the Antarctic via Fremantle of Australia. At Fremantle, Mr. M. SPONHOLZ, American meteorologist, got on board the FUJI as an observer. On December 29, 1967, the FUJI reached the northern part of fast-ice of Lutzow-Holm Bay, 40 nautical miles northeast of Syowa Station, and from there the first helicopter flight to the base was made carrying personnel and cargo. Afterwards the FUJI penetrated the hard fast-ice to make an approach to the station, and after eight days of great efforts she succeeded to approach the station. On Junuary 12, 1968 the FUJI reached coastal bay-ice of the Soya Coast near the station, and unloaded three oversnow vehicles (KD60), sleds and fuels for the scheduled traverse trip to the south pole. Next day the FUJI reached and anchored at the coast of East Ongul Island. Unloading of about 500 tons cargo and transportation to the station was carried out mainly by two S-61A helicopters, of which nearly 140 tons of heavy materials were transported over ice by oversnow vehicles. Construction work was carried out throughout the period of anchorage. A new living hut (wooden, 20m×5m), a new generator hut (metal, 14m×18m) and corridor were almost completed before the ship left. On January 29, the FUJI moved to the southern part of Lutzow-Holm Bay, from where two research parties were sent out, one for the Lang Hovde area and the other for the Skarvs Nes area. In the Lang Hovde area an underwater research was attempted by SCUBA diving. On February 1, the FUJI returned to the Syowa and left there on February 3rd, taking the same route to the north, and escaped from fast-ice after ...